2006
DOI: 10.1256/qj.05.01
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the tropical Atlantic decadal oscillation based on the analysis of the ICOADS

Abstract: SUMMARYFrom an analysis of the International Comprehensive Ocean-Atmosphere Data Set, we were able to confirm salient features of the tropical Atlantic decadal oscillation illustrated in previous works. These features include antisymmetric behaviour of surface air pressure and sea surface temperature with two centres of action residing in the tropical North and South Atlantic Oceans. In addition to the recognized features of the oscillation, we found a new aspect: the principal mechanism regulating the oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Analyses of observations have suggested that the effect on the earth's climate system of the small-amplitude variations in solar radiation that occur during the approximately 11-yr solar cycle [the decadal solar oscillation (DSO)] may produce significant responses in the troposphere (e.g., Haigh 1996Haigh , 2001Haigh , 2003Lean and Rind 2001;Rind 2002;Lean et al 2005;van Loon and Labitzke 1998;van Loon andShea 1999, 2000;Gleisner and Thejll 2003;van Loon et al 2004;Crooks and Gray 2005;Wang et al 2005;Bhattacharyya and Narasimha 2005;Lim et al 2006) and ocean (White et al 1997(White et al , 1998Bond et al 2001;Weng 2005). Specifically for the Indo-Pacific region, van Loon et al (2004van Loon et al ( , 2007 have demonstrated that the state of the climate system during peaks in the DSO resembles cold events (also known as La Niña events) in the Southern Oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of observations have suggested that the effect on the earth's climate system of the small-amplitude variations in solar radiation that occur during the approximately 11-yr solar cycle [the decadal solar oscillation (DSO)] may produce significant responses in the troposphere (e.g., Haigh 1996Haigh , 2001Haigh , 2003Lean and Rind 2001;Rind 2002;Lean et al 2005;van Loon and Labitzke 1998;van Loon andShea 1999, 2000;Gleisner and Thejll 2003;van Loon et al 2004;Crooks and Gray 2005;Wang et al 2005;Bhattacharyya and Narasimha 2005;Lim et al 2006) and ocean (White et al 1997(White et al , 1998Bond et al 2001;Weng 2005). Specifically for the Indo-Pacific region, van Loon et al (2004van Loon et al ( , 2007 have demonstrated that the state of the climate system during peaks in the DSO resembles cold events (also known as La Niña events) in the Southern Oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…We used essentially the same filter devised by Lim et al (2006) and employed also by Suh and Lim (2006) but with different cut-off frequencies. The digital filter was carved based on the wavelet analysis by Torrence and Compo (1998).…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…Lim et al (2006) found that solar irradiance modulation of local and regional relative humidity, in combination with the related climatic distribution of clouds and water vapor over the tropical Atlantic, is sufficient to explain the observed tropical Atlantic decadal oscillation.…”
Section: Arctic-mediated Climate Variation 149mentioning
confidence: 95%
“…The present study indirectly assumes the optimal climatic response filter of the Earth ocean-atmosphere-ice system to peak around such multidecadal to centennial scales, which can be taken to be roughly 50 to 500 years (i.e., much less than 1000 years). The challenge of this research, then, must lie in the identification of relevant and/or dominant centers of climatic action (COAs; Table 1 lists acronyms used in this paper) and interactions among those COAs (Christoforou and Hameed, 1997;Rodionov et al, 2005;Huth et al, 2006;Lim et al, 2006). Huth et al (2006) found a general tendency for atmospheric circulation modes 1 to be more zonal, with COAs covering wider areas and ARCTIC-MEDIATED CLIMATE VARIATION 145 teleconnection among different regions spanning longer distances when solar activity is strong.…”
mentioning
confidence: 99%